2022
DOI: 10.1155/2022/6290064
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Cartilage Intermediate Layer Protein 2 Were Higher in Overweight and Obese Subjects

Abstract: Background. Cartilage intermediate layer protein 2 (CILP2) is associated with a variety of plasma lipoproteins and lipid traits. However, the correlation between CILP2 and obesity remains unknown. The aim of this study was to investigate the relationship between circulating CILP2 levels and obesity based on body mass index (BMI). Methods. A total of 252 subjects were divided into three groups: normal weight ( n = 124 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The CILP2 gene is associated with lipid and cardiovascular diseases in the Asian Malay population [ 19 ]. Furthermore, Li et al (2022), reported for the first time that CILP2 expression in the serum of obese individuals was higher than that in normal individuals [ 20 ]. In conclusion, many current studies suggest an association between CILP2 and lipid metabolism in cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The CILP2 gene is associated with lipid and cardiovascular diseases in the Asian Malay population [ 19 ]. Furthermore, Li et al (2022), reported for the first time that CILP2 expression in the serum of obese individuals was higher than that in normal individuals [ 20 ]. In conclusion, many current studies suggest an association between CILP2 and lipid metabolism in cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%